DIFFUSION INNOVATION BEHAVIOR STUDENT IN WASTE MANAGEMENT SCHOOLS ON SMALL ISLANDS - Ikhwan, Zainul; Hanum, Ulfa; Indris, Fadhil; Puspawati, Catur; WulanSari, Kusrini (International Journal of Social Science, 2023)
This research aims to determine the diffusion of waste management program innovations in schools on Penyengat Island, Tanjungpinang City. This research uses descriptive qualitative methods. Based on the analysis results obtained in the field, it can be concluded that the results found using the Diffusion of Innovation theory by Everet M. Rogers with 4 elements, namely Innovation, Communication Channels, Time Period and Social System, show that the waste management program adoption process will run optimally. This shows that the spirit of intensive communication from the school community on Penyengat Island is enthusiastic about adopting the program due to the sense of ownership of the school, facilities and infrastructure that require development as well as the process of preparing administrative requirements which is slowly increasing with collaboration. More incentive assistance and communication is needed, especially by activating the role of committees at each school in forming the character of students.